Tantangan dan Kendala Penggunaan Bahasa Baku di Kalangan Mahasiswa - Alifa Kamal, Nazla; Usiono, Usiono (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
Standard language has an important role in the world of education, especially among students as the next generation of intellectuals. However, the implementation of standard language in students' daily lives still faces various challenges. This research aims to explore and analyze the factors that influence the use of standard language among students. Using a qualitative approach, data was collected through interviews, observation and document study. The research results show that the main challenges include a lack of understanding of standard language rules, the dominance of regional languages ​​and informal languages, as well as low student motivation and awareness in applying standard language, especially in formal situations. Apart from that, the social environment, such as the communication culture on campus and the use of social media, also contributes to students' language patterns. This research recommends synergy between educational institutions, lecturers and students to improve standard language competence through training programs, familiarization and integration of standard language into academic activities. With these steps, it is hoped that the use of standard language can be implemented more optimally as a symbol of respect for cultural and scientific identity.